Europec 2015 2015
DOI: 10.2118/174323-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Gas Production From Tight, Ultratight and Shale Gas Reservoirs: Flow Regimes and Geomechanical Effects

Abstract: Production from unconventional gas resources (UGRs) has received great attentions because of their large reserves as well as technical advances in developing these reservoirs. The fluid flow in ultralow permeability porous media cannot be considered in the range of conventional Darcy flow as it undergoes a transition from a Darcy regime to slip flow and free molecule flow regimes. Understanding fluid flow inside the matrix and how the matrix permeability evolves over depletion are among the major challenges to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many scholars adopt the continuum mechanics model to investigate the gas flow within shale reservoirs. Specifically, both the single porosity single permeability model [1] and dual porosity dual permeability model [2][3][4][5] are used to represent the gas flow within the shale matrix. For the single porosity model, it is assumed that the porous medium is made up of uniform pores with the same properties, which ignores the differences between big cracks and small pores.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars adopt the continuum mechanics model to investigate the gas flow within shale reservoirs. Specifically, both the single porosity single permeability model [1] and dual porosity dual permeability model [2][3][4][5] are used to represent the gas flow within the shale matrix. For the single porosity model, it is assumed that the porous medium is made up of uniform pores with the same properties, which ignores the differences between big cracks and small pores.…”
Section: Introductionmentioning
confidence: 99%
“…where σ = −σ kk /3 is the mean compressive stress. Combining Equations (1), (2), (7) and (8) yields the general Navier-type equations for the matrix and fracture, respectively…”
Section: Formulation Of Solid Deformationmentioning
confidence: 99%
“…Many scholars established models to investigate the evolution of the permeability of different parts over the past few decades. The models were developed from a single porosity/permeability model [8] to dual porosity/permeability model [9][10][11][12]. For a single porosity model, the effects of effective stress variation and the matrix shrinkage/swelling were taken into consideration [13,14], which ignored the interactions between different range radius pores.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, single-porosity models [7,10], dual-porosity models [22,23], and triple-porosity models (dual fracture models) [24,25] are used to describe gas flow in shale reservoirs. However, single-porosity and dual-porosity models assume that the pore and fracture properties are uniform across the porous medium, while actual shale reservoirs include multiscale pores and fractures with different properties.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In addition to that, the validity of such correlation models using empirical coefficients has been questionable [13][14][15][16][17][18]. Chen et al [19] and Wu et al [5] proposed gas transport models for describing gas flow in different scale fractures while considering the effects of the fracture shape; Mi et al [20] established an apparent permeability model for describing gas flow in multiscale shale reservoirs without considering the effects of adsorption/desorption and stress-sensitivity; Wu et al [3] proposed an apparent permeability model for evaluating gas flow in nano-scale shale matrix by coupling the effects of adsorption/desorption and stress-sensitivity; Sun et al [4] revealed gas flow mechanisms in a shale matrix combined with the effects of surface diffusion and the thickness of the adsorbed gas layer; Zhang et al [21] found that shale reservoirs are highly stress-dependent, which significantly affects gas transport mechanisms; and Moghaddam et al [22] investigated the gas flow mechanisms in multiscale fractures in tight reservoirs while considering the coupled effects of adsorption/desorption and stress-sensitivity. Few previous studies have attempted to model all gas flow regimes in multiscale shale reservoirs while considering multiple effects as reservoir pressure changes [6].…”
Section: Introductionmentioning
confidence: 99%